2021
DOI: 10.1038/s41598-021-85552-4
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography of the lateral abdominal muscles in C-shaped idiopathic scoliosis: a case–control study

Abstract: Considering that knowledge about lateral abdominal muscles (LAM) in idiopathic scoliosis (IS) is still very limited, the aims of this study were: (a) to compare LAM thickness and elasticity between C-shaped IS and non-scoliotic population; and (b) to compare LAM thickness and elasticity between C-shaped thoracic, thoracolumbar, and lumbar IS. A total of 259 adolescents were included in the final analysis; among these, 108 were IS and 151 were non-IS. LAM thickness and elasticity were measured at rest and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Respiratory muscle morphology (mainly the diaphragm and intercostal muscles) can be assessed using ultrasound imaging (US) [6][7][8][9]. Recently, shear wave elastography (SWE) as a new, non-invasive US imaging technique, has allowed the assessment of muscle's mechanical properties [10,11]. It has been suggested that SWE may be used as an index of diaphragmatic force change [12], and that the diaphragm shear modulus measured using SWE is related to transdiaphragmatic pressure [13,14], which is considered the gold standard in diaphragm evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory muscle morphology (mainly the diaphragm and intercostal muscles) can be assessed using ultrasound imaging (US) [6][7][8][9]. Recently, shear wave elastography (SWE) as a new, non-invasive US imaging technique, has allowed the assessment of muscle's mechanical properties [10,11]. It has been suggested that SWE may be used as an index of diaphragmatic force change [12], and that the diaphragm shear modulus measured using SWE is related to transdiaphragmatic pressure [13,14], which is considered the gold standard in diaphragm evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, B-mode ultrasound imaging (USI) has been used to assess muscles' geometry. In some cases, USI has been used to assess lateral abdominal muscles (LAMs) thickness or thickness change at rest and during various movements because the potential role of LAM in low back pain (LBP) [1][2][3] and scoliosis [4][5][6][7][8][9][10][11] was verified. Recently, quantitative shear wave ultrasound elastography (SWE) has also been developed and used to study muscle shear modulus [12] and refer it to muscles' elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies evaluating muscle stiffness with SWE and investigating muscle imbalance have been conducted to clarify the etiology of scoliosis. It has been suggested that this asymmetrical load may be caused by the paravertebral and lateral abdominal muscles consisting of the transversus abdominis (TrA), obliquus internal (OI), and obliquus external (OE) [32,33]. Liu the convex side of scoliosis [32].…”
Section: Adolescent Idiopathic Scoliosismentioning
confidence: 99%
“…Liu the convex side of scoliosis [32]. In a study examining the stiffness of the lateral abdominal muscles (TrA, OI, and OE), it was stated that there were no differences between healthy control and AIS groups in terms of muscles stiffness at rest and during isometric contraction and also there was no muscles stiffness asymmetry between the concave and the convex sides of scoliosis [33]. In addition, the same research group found that stiffness measurements of the lateral abdominal muscles were carried out with high reliability/agreement during contraction, while the reliability of the stiffness measurements ranged from moderate to excellent at rest [34].…”
Section: Adolescent Idiopathic Scoliosismentioning
confidence: 99%